2011
DOI: 10.1080/10548408.2011.546209
|View full text |Cite
|
Sign up to set email alerts
|

Film-Induced Tourism as a Vehicle For Destination Marketing: Is it Worth the Efforts?

Abstract: This study examined the impact of a film on the featured destination's image and travel intentions through comparing the results of a one-group pretest-posttest quasi-experiment. Then, the effect of destination attributes and overall image on travel intentions is examined simultaneously through path analysis. The results indicate that the role of the overall image as a mediating variable is not significant as respondents relied more on specific destination image attributes on their intention to visit. This was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 63 publications
5
39
0
7
Order By: Relevance
“…Baloglu, 2000;Chen and Tsai, 2007;Hahm and Wang, 2011;Lee, 2009;Nadeau et al, 2008;Wang et al, 2010;Zhang et al, 2014). However, according to Echtner and Ritchie's (1993) seminal research, qualitative or unstructured data provides a more unique and holistic destination image due to the fact that respondents are able to express their perceptions in their own words.…”
Section: Literature Review Destination Imagementioning
confidence: 99%
“…Baloglu, 2000;Chen and Tsai, 2007;Hahm and Wang, 2011;Lee, 2009;Nadeau et al, 2008;Wang et al, 2010;Zhang et al, 2014). However, according to Echtner and Ritchie's (1993) seminal research, qualitative or unstructured data provides a more unique and holistic destination image due to the fact that respondents are able to express their perceptions in their own words.…”
Section: Literature Review Destination Imagementioning
confidence: 99%
“…Much of the existing research on filminduced tourism has measured the impact of media productions on people's perceptions of places while also determining the nature and extent to which these images shape the travel decisions and experiences of tourists (e.g., Young and Young 2008;Hahm and Wang 2011;Hudson et al 2011). Underlying many of these studies is the belief that film tourism can significantly benefit local economies, increase publicity and recognition of destinations, expand infrastructure, and revitalize communities.…”
Section: Such a Perspective Offers A Fuller Recognition Of The Materimentioning
confidence: 99%
“…This study found that the film directly influenced the audiences; the audiences directly captured the positive and the negative specific images of destination from the film. The image that respondents had became more detailed, and they declared the strong intention to travel after watching the film (Hahm & Wang, 2011).…”
Section: Types Of Mediamentioning
confidence: 99%
“…Watching movies is a major leisure activity throughout the world (Kim & Richardson, 2003). In study of Hahm and Wang (2011), they mentioned that film is one of the most important motivational mass media for tourism. Film tourism is defined as tourist visits to a screened location that was featured in film, television, or video, also referred to as movie-induced tourism (Hudson & Ritchie, 2006).…”
Section: Types Of Mediamentioning
confidence: 99%
See 1 more Smart Citation